Implementasi Manajemen Sarana Prasarana dalam Meningkatkan Mutu Pembelajaran di PAUD Melati Karawang - Wulandari, Alifia Putri; Darmiyanti, Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Resource management is critical to learning. This study aims to explain facilities and infrastructure management: planning, implementation and evaluation. Factors that support and hinder the management of facilities and infrastructure to improve the quality of learning at PAUD Melati Karawang. This qualitative descriptive study has beeb carried out. This study involved school principals and teachers at PAUD Melati Karawang. Data was collected through interviews, observatiob, documentation and field notes. Management of strategies and resources to improve the quality of learning: 1) Anticipating which involves in-depth analysis of needs, examining conditions and circumstances and ensuring that work meetings are arranged between teachers and school principals; 2) All aspects of implementation including procurement, use and maintenance; 3) Evaluation using work meeting data; 4) Factors that support management and use of resources to improve the quality of learning at PAUD Melati Karawang. Therefore, by using teaching materials through teaching aids, using teaching aids that are available both inside and outside using the current environment. Inhibiting factors, such as lack of funds. Therefore, it can be said that the management of facilities and infrastructure at PAUD Melati Karawang is quite good and can make the learning space enjoyable.